New developments in Semiclassical Transition-State Theory - Shan, X; Burd, T; Clary, D (American Chemical Society, 2019)
This Feature Article describes some recent developments and applications of the Semiclassical Transition-State Theory (SCTST) for treating quantum tunneling in chemical reactions. A reduced dimensional form of the SCTST is discussed and is shown to be particularly efficient, as the required number of electronic structure calculations is reduced to an absolute minimum. We also describe how an alternative formulation of SCTST developed by Hernandez and Miller [ Chem. Phys. Lett. 1993, 214, 129], the SCTST-θ, has advantages in allowing for straightforward applications of the SCTST for any form of the potential expansion at the transition state. We also illustrate the power of SCTST in applications to more complex systems. We show how polyatomic modes such as internal rotations and torsions can be treated efficiently in SCTST calculations. We also describe some applications of the method to hydrogen atom tunneling in unimolecular reactions including the degradation of chemical nerve agents and the decay of the atmospherically important Criegee intermediates.